2020
DOI: 10.1007/s00259-020-05002-7
|View full text |Cite
|
Sign up to set email alerts
|

Head-to-head comparison of DFO* and DFO chelators: selection of the best candidate for clinical 89Zr-immuno-PET

Abstract: Purpose Almost all radiolabellings of antibodies with 89 Zr currently employ the hexadentate chelator desferrioxamine (DFO). However, DFO can lead to unwanted uptake of 89 Zr in bones due to instability of the resulting metal complex. DFO*-NCS and the squaramide ester of DFO, DFOSq, are novel analogues that gave more stable 89 Zr complexes than DFO in pilot experiments. Here, we directly compare these linker-chelator systems to identify optimal immuno-PET reagents. Methods Cetuximab, trastuzumab and B12 (non-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 38 publications
(56 reference statements)
2
58
0
Order By: Relevance
“…When comparing the performance of these chelators, it appears that the octadentate analog of DFO consisting of 4 hydroxamate moieties, called DFO* (''DFO star''), is able to solve the instability issues observed with 89 Zr-DFO (Fig. 1) (17). Because the bifunctional variant DFO*-NCS is now commercially available, its translation to the clinic can be expected soon.…”
Section: Zr-labeled Tracer Productionmentioning
confidence: 99%
“…When comparing the performance of these chelators, it appears that the octadentate analog of DFO consisting of 4 hydroxamate moieties, called DFO* (''DFO star''), is able to solve the instability issues observed with 89 Zr-DFO (Fig. 1) (17). Because the bifunctional variant DFO*-NCS is now commercially available, its translation to the clinic can be expected soon.…”
Section: Zr-labeled Tracer Productionmentioning
confidence: 99%
“…In most cases, their performance is assessed in comparison to the current standard DFO. While this practice is well justified, a direct comparison among the new chelators for the identification of the most promising candidate(s) for clinical translation is, with few exceptions [28,44,45,48], still pending. Along these lines, a standardization of in vitro experiments studying the stability of 89 Zr-complexes would be highly desirable to facilitate a direct comparison of reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vivo studies on the intratibial BT-474 model showed much better tumor-to-background contrast due to less unspecific accumulation of 89 Zr in bones. The authors concluded that DFO-immunoconjugates are less suitable for the detection of bone metastases and again highlighted the superiority of DFO* derivatives in comparison to the current gold standard DFO [44].…”
Section: Dfo Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the octadentate version of the DFO chelator, the so-called DFO*, has been developed. Two different functionalized versions of this chelator were synthesized, conjugated with a monoclonal antibody, and tested in vivo showing a lower 89 Zr bone uptake over the DFO conjugate [ 24 ]. Nowadays, the development of radiotracers for PET imaging is focused on the use of antibodies or antibodies fragments as carriers.…”
Section: Introductionmentioning
confidence: 99%